THE INFLUENCE OF LEADERSHIP STYLE AND EMPLOYEE PRODUCTIVITY TOWARD ORGANIZATIONAL PERFORMANCE WITH ASSOCIATION TO THE EXTERNAL STAKEHOLDER POINT OF VIEW - Amar, M. Yunus (Journal of Management and Business, 2012)
The objectives of the researces are to observe : (1) The impact of leadership style upon the employees’ productivity; (2). The impact of leadership style and employees’ productivity upon the company’s financial performance; (3). The correlation between financial performance and satisfaction level of each company’s external stakeholder ( the supplier, customers, and activist groupsj.The research is conducted in the companies that operate base metal industries in Sulawesi The methode in use is the census, and the data collection is carried out by using questionares. The collected data is data population, and they are analysed by using statistical methodes, namely : (1) Path Analysis to observe the impact of leadership style upon employees’ productivity and the impact of leadership style plus employees’ productivity upon the company’s financial performance. (2). Product Moment Perason Correlation to observe the correlation between finacial performance and the satisfaction level of of each company’s external stakeholder ( the suppliers, customers, and activist groups). After conducting the tests upon the hypotheses, the researcer indicates that (1) The leadership style has positive impact upon the employees’ productivity. (2). The leadership style together with the employees’ productivity give positive impact upon the company’s financial performance, and (3) The company’s financial performance has positive correlation with the satisfaction level of each company’s external stakeholder (the suppliers, customers, and activist groups )